Настання та притягнення до юридичної відповідальності за порушення земельного законодавства: практична необхідність у визначенні - Галагуза, А. В.; Галагуза, А. В.; Galaguza, А. (My University, 2013)
In the article has been done analysis of position of Constitutional Court of Ukraine on questions of offensive and bringing in to liability (decision № of 9-рп/99 from October, 27, 1999), and, using principles of differentiation of problem concepts fixed in him, has been done suppositions concerning the definition of these moments in the field of application of legal liability for violation of land legislation.
Галагуза А. В. Настання та притягнення до юридичної відповідальності за порушення земельного законодавства: практична необхідність у визначенні / А. В. Галагуза // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 381-388.
Keywords: порушення земельного законодавства в Україні; позиція Конституційного Суду України щодо порушень земельного законодавства; настання юридичної відповідальності за порушення земельного законодавства в Україні; нарушения земельного законодательства в Украине; позиция Конституционного Суда Украины по нарушениям земельного законодательства; наступление юридической ответственности за нарушения земельного законодательства Украины; violations of land legislation in Ukraine; the position of the Constitutional Court of Ukraine for violations of land legislation; offensive legal responsibility for violations of land legislation of Ukraine